2007
DOI: 10.1111/j.1365-2648.2007.04389.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to evidence‐based nursing: a focus group study

Abstract: Title. Barriers to evidence-based nursing: a focus group study Aim. This paper reports a study to explore the barriers to evidence-based nursing among Flemish (Belgian) nurses. Background. Barriers obstructing the call for an increase in evidence-based nursing have been explored in many countries, mostly through quantitative study designs. Authors report on lack of time, resources, evidence, authority, support, motivation and resistance to change. Relationships between barriers are seldom presented. Methods. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 35 publications
5
61
0
12
Order By: Relevance
“…Recent findings of a focus group-based study indicate that nurses still have limited space for autonomous decisions under the supervision of doctors. They stated that physicians are more willing to take advice from physiotherapists (Hannes et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings of a focus group-based study indicate that nurses still have limited space for autonomous decisions under the supervision of doctors. They stated that physicians are more willing to take advice from physiotherapists (Hannes et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is not quite clear whether the low number of empirical, in-depth qualitative studies found is due to a lack of qualitative research being conducted, researchers' reluctance to submit to physiotherapy journals, or reluctance of the journals to accept qualitative studies (Gibson and Douglas, 2003). While qualitative studies listing the barriers to the implementation of EBP in doctors, nurses, and dentists have been conducted in Belgium (Hannes et al, 2005;Hannes et al, 2007;Hannes et al, 2008b), no such studies have been done in the physiotherapy profession. We aimed to perform a context-specific research study to answer the question: ''What barriers do Belgian (Dutch-speaking) physiotherapists meet when trying to use evidence in practice?''…”
Section: Introductionmentioning
confidence: 99%
“…This appears to be consistent with international literature and therefore contributes to the validation of our findings. However, it was noticed that many of these concerns have been mentioned by other health care practitioners as well (Hannes et al 2005(Hannes et al , 2007(Hannes et al , 2008a(Hannes et al , b, 2009Schofield et al 2006). A recent study comparing obstacles experienced by psychiatrists with obstacles experienced in other health care disciplines revealed that general practitioners and physiotherapists also experience a broad variety of complex problems and difficulties to diagnose patients during the first encounter (Hannes et al 2008b).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing obstacles experienced by psychiatrists with obstacles experienced in other health care disciplines revealed that general practitioners and physiotherapists also experience a broad variety of complex problems and difficulties to diagnose patients during the first encounter (Hannes et al 2008b). Nurses state to be focussed on their relationship with patients as well and are often confronted with patients' psychological and social problems, especially those working in the home environment (Hannes et al 2007). Whether or not certain obstacles are typical to the psychiatric discipline needs careful consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation